Prevention of diabetes in nonobese diabetic mice by anti-I-A monoclonal antibodies: transfer of protection by splenic T cells. - Boitard, C (1988)
The nonobese diabetic (NOD) mouse has been developed as a model for insulin-dependent diabetes. One gene required for the development of diabetes is associated with the major histocompatibility complex. This gene possibly could be linked to class II genes, which show a unique pattern in NOD mice. To evaluate the role of the I-A class II antigen expressed in NOD mice, we studied the effect of anti-I-A monoclonal antibodies on disease onset in vivo. Long-term treatment with anti-class II IgG2a antibodies specific for NOD I-A antigen prevented the spontaneous development of diabetes, as opposed to control antibodies shown not to react with NOD I-A antigen. Anti-class II antibodies apparently elicited active immune suppression, requiring a fully immunocompetent host, rather than passive blockade of class II antigen. Treatment with anti-class II antibody effectively prevented the adoptive transfer of diabetes produced by splenocytes from diabetic NOD mice into newborn mice but failed to prevent adoptive transfer into irradiated adult NOD recipients. Direct evidence for the induction of suppressor cells was obtained from the passive transfer of spleen cells from anti-class II antibody-treated NOD donors. The injection of anti-class II antibody-treated spleen cells collected from NOD donors prevented the development of diabetes, which normally follows transfer of diabetogenic spleen cells into irradiated 8-week-old male NOD recipients. Depletion experiments indicate that CD4+ cells are responsible for anti-class II-induced protection transferred by spleen cells.